Kajian Literatur: Validasi Metode Multiplex Real Time Polymerase Chain Reaction (Real Time PCR) Pada Identifikasi Babi: Review Article: Validation of Multiplex Real-Time Polymerase Chain Reaction (Real-Time PCR) Method in Pork Identification - Chandra Kartika Nawangsari; Rochmy Istikharah; Muhammad Hatta Prabowo (Jurnal Ilmiah Pangan Halal, 2025)
Intentional mixing or contamination by other animal species in products often occurs for various purposes. In Indonesia, where religious freedom is highly valued, halal compliance is a sensitive issue, making halal assurance essential. To detect pork contamination, a validated, efficient, and reliable method is required. One such method is the multiplex Real-Time Polymerase Chain Reaction (multiplex Real-Time PCR). This scoping review aims to identify biomarkers used for porcine DNA analysis with this method. The findings show that its effectiveness is influenced by the detection basis, number of cycles, and annealing temperature. Variation in target DNA alsoaffects analysis results, as target selection determines specificity and sensitivity. Overall, multiplex Real-Time PCR can detect small amounts of DNA with high accuracy, making it relevant for food monitoring and halal authentication. Hence, this study provides insights for stakeholders in the food, cosmetic, and pharmaceutical industries regarding more accurate detection of pork contamination using multiplex Real-Time PCR.